A high temperature resistant and durable antibacterial agent

By preparing high-temperature-resistant and long-lasting antibacterial agents, using a combination technology of modified polymer film and porous silicone surface, combined with hot press fuse and silver nitrate solution, the problem of existing antibacterial agents being prone to failure in high temperature environments is solved, and high efficiency is achieved , lasting sterilization effect and higher human safety.

CN115530162BActive Publication Date: 2025-02-14HEILONGJIANG CRESHUS PETROLEUM TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210988720.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-09
Publication Date
2025-02-14
Estimated Expiration
2041-12-09

AI Technical Summary

Technical Problem

Existing antibacterial agents are prone to failure in high temperature environments and are insufficient in safety and durability to the human body, making it difficult to have effective sterilization effects under the premise of health and environmental protection.

Method used

By preparing a high-temperature-resistant and long-lasting antibacterial agent, a modified polymer film and porous silica gel surface are formed by using primary deposition and secondary deposition steps, and combined with hot press fuse and silver nitrate solution treatment, an antibacterial agent with carbon dioxide molecular switching function is formed.

Benefits of technology

It achieves effective antibacterial performance under high temperature environments and has a more lasting bactericidal effect, avoids the loss of silver ions and nitrates, and improves the safety and service life of antibacterial agents.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a high temperature resistant and durable antibacterial agent, and relates to the technical field of antibacterial materials. When preparing the high temperature resistant and durable antibacterial agent, the present invention first uses iodomethane and 8-amino-1-octene to react to obtain a quaternary ammonium salt, performs a primary deposition, and adds acrylic acid during the polymerization deposition of the quaternary ammonium salt to obtain a modified polymer film, and then uses tetraethyl orthosilicate to perform a secondary deposition on the modified polymer film to form a porous silica gel surface to obtain a composite film, and after the surface of one side of the composite film is infiltrated with a silver nitrate solution, the infiltrated surfaces of the two composite films are bonded and hot-pressed and fused, and finally packaged into bags to obtain the high temperature resistant and durable antibacterial agent. The high temperature resistant and durable antibacterial agent prepared by the present invention has good high temperature resistance, durability and antibacterial properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of antibacterial materials, in particular to a high-temperature resistant and durable antibacterial agent. Background Art

[0002] Antimicrobial agents are a type of agent used to prevent and treat plant diseases caused by various pathogenic microorganisms. They have a killing effect or growth inhibition effect on pathogenic microorganisms. Antimicrobial agents are generally divided into inorganic antimicrobial agents, organic antimicrobial agents and natural antimicrobial agents.

[0003] With the development of society, people have higher and higher requirements for antibacterial agents. While meeting the antibacterial properties, they are required to be non-toxic to the human body and not produce gases or substances harmful to the human body during use. Inorganic antibacterial agents use metal ions, which are costly and most of them are toxic. Organic antibacterial agents are easily hydrolyzed and easily volatilize when heated to produce organic gases. Although natural antibacterial agents are healthy and environmentally friendly, they have poor heat resistance and low sterilization efficiency. In order to have an effective sterilization effect while being healthy and environmentally friendly, the antibacterial agent prepared by the present invention is designed with a carbon dioxide molecular switch, which can recognize the carbon dioxide produced by bacteria decomposing organic matter and sterilize, and has good heat resistance. Summary of the invention

[0004] The purpose of the present invention is to provide a high temperature resistant and durable antibacterial agent and a preparation method thereof, so as to solve the problems existing in the prior art.

[0005] A method for preparing a high temperature resistant and durable antibacterial agent mainly comprises the following preparation steps: primary deposition, secondary deposition, hot pressing and fusing, and packaging.

[0006] As an optimization, the preparation method of the high temperature resistant and durable antibacterial agent mainly includes the following preparation steps:

[0007] (1) Primary deposition: octenyl ammonium salt, acrylic acid and anhydrous ethanol are mixed evenly in a mass ratio of 3:1:10, and then a catalyst of 0.01 to 0.03 times the mass of octenyl ammonium salt is added, and a straight deposition film with a thickness of 0.5 to 0.8 mm is obtained at 50 to 60 °C, and then washed with anhydrous ethanol for 3 to 5 times, and dried at 60 to 70 °C for 4 to 6 hours to obtain a modified polymer film;

[0008] (2) Secondary deposition: fix the modified polymer film on a glass plate and treat it with an organic silicon deposition liquid, soak the surface with an organic silicon deposition liquid of 0.8 to 1.2 times the mass of the modified polymer film, irradiate the surface with ultraviolet light, and then immerse it in an organic silicon deposition liquid of 20 to 25 times the mass of the modified polymer film, let it stand at 20 to 30°C for 1 to 2 hours, turn the modified polymer film over so that the surface not treated with the organic silicon deposition liquid faces up and fix it on a glass plate, repeat the organic silicon deposition liquid treatment steps, then soak it with 10% sodium hydroxide by mass for 20 to 30 minutes, and wash it with pure water and anhydrous ethanol for 3 to 5 times in sequence, and dry it at -10 to -1°C and a pressure of 5 to 10Pa for 6 to 8 hours to obtain a composite film;

[0009] (3) Hot-pressing fusing: Infiltrate one side of the composite membrane with a 10% silver nitrate solution of 0.3-0.5 times the mass of the composite membrane, place the wetted surfaces of two composite membranes together for hot pressing, cool to 10-30°C, and then fuse them with an electric heating wire fuser, then rinse with a 1-5°C 8% sodium bicarbonate solution for 3-5 minutes, wash with pure water for 3-5 times, and dry at 60-70°C for 6-8 hours to obtain an antibacterial agent;

[0010] (4) Packaging: Use a packaging machine to put the antimicrobial agent into packaging paper and pack it into bags. The packaging weight of each bag is 3 to 4 grams to obtain a high-temperature resistant and long-lasting antimicrobial agent.

[0011] As an optimization, the preparation method of the octenyl quaternary ammonium salt in step (1) is as follows: 8-amino-1-octene, iodomethane and a 10% sodium hydroxide solution are uniformly mixed in a mass ratio of 1:5:3, and then 0.01 to 0.03 times the mass of 8-amino-1-octene sodium iodide is added, and the mixture is stirred at 30 to 40°C and 500 to 800 r / min for 4 to 6 hours, and then heated to 50 to 60°C and maintained for 20 to 30 minutes, cooled to 1 to 5°C and filtered, and rinsed with a 1 to 5°C sodium bicarbonate solution with a mass fraction of 8% for 3 to 5 minutes, and then washed with 1 to 5°C pure water for 3 to 5 times, and dried for 6 to 8 hours under the conditions of 1 to 10Pa and -10 to -1°C.

[0012] As an optimization, the catalyst in step (1) is prepared by uniformly mixing titanium tetrachloride and triethylaluminum in a mass ratio of 5:3.

[0013] As an optimization, the organic silicon deposition liquid in step (2) is ethyl orthosilicate, which is uniformly mixed with 10% by mass of ammonia water and anhydrous ethanol in a mass ratio of 1:10:10.

[0014] As an optimization, the process parameters of the ultraviolet radiation in step (2) are: ambient temperature 20-30°C, ultraviolet lamp power 60-70W, ultraviolet wavelength 300-380nm, and radiation time 8-10min.

[0015] As an optimization, the process parameters of the hot pressing in step (3) are: temperature 100~120°C, pressure 0.3~0.5MPa, and hot pressing time 20~30min.

[0016] As an optimization, the process parameters of the electric heating wire fusing machine in step (3) are: electric heating wire temperature 300-320°C, fusing distance 1cm, and fusing mode orthogonal fusing.

[0017] As an optimization, the high-temperature resistant and durable antibacterial agent prepared by the preparation method of the high-temperature resistant and durable antibacterial agent mainly includes, by weight: 3 to 5 parts of modified polymer film, 150 to 250 parts of silicone deposition liquid and 1 to 2 parts of silver nitrate solution; the modified polymer film is formed by adding acrylic acid copolymer during the polymerization film formation process of octenyl quaternary ammonium salt; the silicone deposition liquid is prepared from tetraethyl orthosilicate, ammonia water and anhydrous ethanol.

[0018] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0019] When preparing the high temperature resistant and durable antibacterial agent, the present invention firstly performs a deposition to obtain a modified polymer film, then performs a secondary deposition to form a porous silica gel surface to obtain a composite film, and then performs hot pressing and fusing, and obtains the high temperature resistant and durable antibacterial agent after packaging.

[0020] Firstly, acrylic acid is added to the process of octenyl quaternary ammonium salt polymerization film formation to polymerize and obtain a modified polymer film. The quaternary ammonium cations on the modified polymer film can be combined with carboxyl anions through electrostatic force, thereby reducing the loss and damage of the quaternary ammonium cations and increasing the service life. When in use, the carbon dioxide produced by the decomposition and corrosion of organic matter by bacteria can inhibit the dehydrogenation of carboxyl groups to form negative ions. The quaternary ammonium cations are separated from the modified polymer film and bound on the surface to form molecular thorns, which pierce the bacteria with their fat-soluble long carbon chains and eventually inactivate the bacteria, thereby having a sterilization effect through the control of the carbon dioxide molecular switch; deposition is performed on the surface of the modified polymer film to form a porous silica gel surface to obtain a composite film. The porous silica gel surface is water-absorbent and the surrounding environment is dried by adsorbing water molecules to achieve the effect of inhibiting bacterial growth. When the bacteria are adsorbed on the porous silica gel surface with water vapor, they can cooperate with the quaternary ammonium cations on the modified polymer film to sterilize. At the same time, the free silanol groups on the surface of the porous silica gel have good bonding and adsorption effects with each other and with metal ions, thereby being easy to be hot-pressed and fixed and adsorbed with silver nitrate.

[0021] Secondly, the porous silica gel surface on one side of the composite membrane is infiltrated with silver nitrate solution, and the porous silica gel surfaces of two composite membranes infiltrated with silver nitrate solution are attached and hot pressed. Silver ions can combine with the silanol groups on the surface of the porous silica gel by silicon-oxygen bonds. At the same time, the porous structure intercepts part of the silver nitrate, which is then fused to obtain an antibacterial agent. During use, when there are too many bacteria, too much carbon dioxide is produced, so that the quaternary ammonium cations can combine with the carboxyl anions to form a carbon dioxide molecular switch that is fully opened to form a channel. At this time, some silver ions and nitrates reach the external environment through the channel for sterilization, which further improves the antibacterial property of the antibacterial agent. When there are a small number of bacteria, the external quaternary ammonium cations directly kill bacteria, and the channel is not fully opened, which prevents the loss of silver ions and nitrates, and makes the antibacterial agent have a more lasting bactericidal performance. DETAILED DESCRIPTION

[0022] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0023] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the high temperature resistant and durable antibacterial agent prepared in the following examples are as follows:

[0024] Antibacterial performance: The high temperature resistant and durable antibacterial agent obtained in each embodiment and the comparative example material were taken with the same mass, and the antibacterial rate was tested according to the Quine test method.

[0025] High temperature resistance and durability: The same mass of the high temperature resistant and durable antibacterial agent obtained in each embodiment and the comparative material were placed in an environment of 100°C for 30 days, and the 30-day antibacterial rate was tested by the Quine test method. The performance retention rate was calculated as 30-day antibacterial rate / initial antibacterial rate.

[0026] Example 1

[0027] A high temperature resistant and durable antibacterial agent mainly comprises, by weight, 5 parts of modified polymer film, 150 parts of organosilicon deposition liquid and 1 part of silver nitrate solution.

[0028] A method for preparing a high temperature resistant and long-lasting antibacterial agent, the method for preparing the high temperature resistant and long-lasting antibacterial agent mainly comprises the following preparation steps:

[0029] (1) Primary deposition: 8-amino-1-octene, iodomethane and 10% sodium hydroxide solution were mixed in a mass ratio of 1:5:3, and then 0.01 times the mass of 8-amino-1-octene sodium iodide was added. The mixture was stirred at 500 r / min at 30°C for 6 h, then heated to 50°C and maintained for 30 min, cooled to 1°C and filtered, rinsed with 1°C 8% sodium bicarbonate solution for 5 min, and then washed with 1°C pure water for 5 min. 1. The octenyl ammonium salt was mixed evenly with acrylic acid and anhydrous ethanol in a mass ratio of 3:1:10, and then a catalyst prepared by mixing titanium tetrachloride and triethylaluminum in a mass ratio of 5:3 with a mass ratio of 0.01 times the mass of the octenyl ammonium salt was added, and a straight deposition film with a thickness of 0.5 mm was obtained at 50°C, and then washed with anhydrous ethanol for 3 times, and dried at 60°C for 6 hours to obtain a modified polymer film.

[0030] (2) Secondary deposition: The modified polymer film was fixed on a glass plate and treated with an organic silicon deposition liquid. Ethyl orthosilicate, 10% by mass ammonia water and anhydrous ethanol were mixed uniformly in a mass ratio of 1:10:10 to prepare an organic silicon deposition liquid. The surface was infiltrated with an organic silicon deposition liquid of 0.8 times the mass of the modified polymer film. The surface was irradiated with an ultraviolet lamp with a power of 60 W and a wavelength of 300 nm at 20°C for 10 min. The surface was then immersed in an organic silicon deposition liquid of 20 times the mass of the modified polymer film. The surface was allowed to stand at 20°C for 2 h. The modified polymer film was turned over so that the surface not treated with the organic silicon deposition liquid faced upward and was fixed on a glass plate. The organic silicon deposition liquid treatment steps were repeated. The surface was then washed with 10% by mass sodium hydroxide for 20 min. The surface was washed with pure water and anhydrous ethanol three times in sequence. The surface was dried at -10°C and a pressure of 5 Pa for 8 h to obtain a composite film.

[0031] (3) Hot-pressing fusing: soak one side of the composite membrane with a 10% silver nitrate solution of 0.3 times the mass of the composite membrane, place the wetted surfaces of the two composite membranes together, press at 100°C and a pressure of 0.3 MPa for 30 min, cool to 10°C and then fuse with an electric heating wire fuser, the heating wire temperature is 300°C, the fuse spacing is 1 cm, and the fuse mode is orthogonal fusing. Rinse with 1°C sodium bicarbonate solution of 8% by mass for 5 min, wash with pure water 3 times, and dry at 60°C for 8 h to obtain an antibacterial agent.

[0032] (4) Packaging: The antimicrobial agent is put into packaging paper and packaged into bags using a packaging machine. The packaging weight of each bag is 3 g, thereby obtaining a high temperature resistant and long-lasting antimicrobial agent.

[0033] Example 2

[0034] A high temperature resistant and durable antibacterial agent mainly comprises, by weight, 4 parts of modified polymer film, 200 parts of organosilicon deposition liquid and 1 part of silver nitrate solution.

[0035] A method for preparing a high temperature resistant and long-lasting antibacterial agent, the method for preparing the high temperature resistant and long-lasting antibacterial agent mainly comprises the following preparation steps:

[0036] (1) Primary deposition: 8-amino-1-octene, iodomethane and 10% sodium hydroxide solution were mixed in a mass ratio of 1:5:3, and then 0.02 times the mass of 8-amino-1-octene sodium iodide was added. The mixture was stirred at 35°C and 600 r / min for 5 h, then heated to 55°C and maintained for 25 min, cooled to 3°C and filtered, rinsed with 3°C 8% sodium bicarbonate solution for 4 min, and then washed with 3°C pure water for 4 times. Drying for 7 hours at 5Pa and -5°C to obtain octenyl ammonium salt, mixing octenyl ammonium salt, acrylic acid and anhydrous ethanol in a mass ratio of 3:1:10, adding 0.01-0.03 times the mass of octenyl ammonium salt and a catalyst prepared by mixing titanium tetrachloride and triethylaluminum in a mass ratio of 5:3, depositing at 55°C to obtain a straight deposition film with a thickness of 0.6 mm, washing with anhydrous ethanol for 4 times, and drying at 65°C for 5 hours to obtain a modified polymer film;

[0037] (2) Secondary deposition: The modified polymer film was fixed on a glass plate and treated with an organic silicon deposition liquid. Ethyl orthosilicate, 10% ammonia water and anhydrous ethanol were mixed in a mass ratio of 1:10:10 to prepare an organic silicon deposition liquid. The surface was soaked with an organic silicon deposition liquid of 0.1 times the mass of the modified polymer film. The surface was irradiated with an ultraviolet lamp with a power of 65 W and a wavelength of 340 nm at 25°C for 9 minutes. The surface was immersed in an organic silicon deposition liquid of 23 times the mass of the modified polymer film. The surface was allowed to stand at 25°C for 1 hour. The modified polymer film was turned over so that the surface not treated with the organic silicon deposition liquid faced upward and was fixed on a glass plate. The organic silicon deposition liquid treatment steps were repeated. The surface was then rinsed with 10% sodium hydroxide for 25 minutes. The surface was washed with pure water and anhydrous ethanol four times in sequence. The surface was dried at -5°C and a pressure of 8 Pa for 7 hours to obtain a composite film.

[0038] (3) Hot-pressing fusing: soak one side of the composite membrane with a 10% silver nitrate solution of 0.4 times the mass of the composite membrane, and place the wetted surfaces of the two composite membranes together. Press them at 110°C and 0.4 MPa for 25 min. After cooling to 20°C, melt them with a heating wire fusing machine. The heating wire temperature is 310°C, the fusing interval is 1 cm, and the fusing method is orthogonal fusing. Rinse with a 3°C sodium bicarbonate solution of 8% by mass for 4 min, wash with pure water 4 times, and dry at 65°C for 7 h to obtain the antibacterial agent.

[0039] (4) Packaging: The antimicrobial agent is put into packaging paper and packaged into bags using a packaging machine. The packaging weight of each bag is 3 g, thereby obtaining a high temperature resistant and long-lasting antimicrobial agent.

[0040] Example 3

[0041] A high temperature resistant and durable antibacterial agent mainly comprises, by weight, 5 parts of modified polymer film, 250 parts of organic silicon deposition liquid and 2 parts of silver nitrate solution.

[0042] A method for preparing a high temperature resistant and long-lasting antibacterial agent, the method for preparing the high temperature resistant and long-lasting antibacterial agent mainly comprises the following preparation steps:

[0043] (1) Primary deposition: 8-amino-1-octene, iodomethane and 10% sodium hydroxide solution were mixed in a mass ratio of 1:5:3, and then 0.03 times the mass of 8-amino-1-octene sodium iodide was added. The mixture was stirred at 800 r / min at 40°C for 4 h, then heated to 60°C and maintained for 20 min, cooled to 5°C and filtered, rinsed with 5°C 8% sodium bicarbonate solution for 3 min, and then washed with 5°C pure water for 3 min. The mixture was dried for 6 hours at 10Pa and -1°C to obtain octenyl ammonium salt. The octenyl ammonium salt, acrylic acid and anhydrous ethanol were mixed uniformly at a mass ratio of 3:1:10, and a catalyst prepared by mixing titanium tetrachloride and triethylaluminum at a mass ratio of 5:3 with a mass ratio of 0.03 times the mass of the octenyl ammonium salt was added. The mixture was deposited at 60°C to obtain a straight deposition film with a thickness of 0.8 mm. The mixture was then washed with anhydrous ethanol for 5 times and dried at 70°C for 4 hours to obtain a modified polymer film.

[0044] (2) Secondary deposition: The modified polymer film was fixed on a glass plate and treated with an organic silicon deposition liquid. Ethyl orthosilicate, 10% by mass ammonia water and anhydrous ethanol were mixed uniformly in a mass ratio of 1:10:10 to prepare an organic silicon deposition liquid. The surface was infiltrated with an organic silicon deposition liquid 1.2 times the mass of the modified polymer film. The surface was irradiated with an ultraviolet lamp with a power of 70 W and a wavelength of 380 nm at 30°C for 8 minutes. The surface was then immersed in an organic silicon deposition liquid 25 times the mass of the modified polymer film. The surface was allowed to stand at 30°C for 1 hour. The modified polymer film was turned over so that the surface not treated with the organic silicon deposition liquid faced upward and was fixed on a glass plate. The organic silicon deposition liquid treatment steps were repeated. The surface was then washed with 10% by mass sodium hydroxide for 30 minutes. The surface was washed with pure water and anhydrous ethanol for 5 times in sequence. The surface was dried at -1°C and a pressure of 10 Pa for 6 hours to obtain a composite film.

[0045] (3) Hot-pressing fusing: soak one side of the composite membrane with a 10% silver nitrate solution of 0.5 times the mass of the composite membrane, and place the wetted surfaces of the two composite membranes together. Press them at 120°C and a pressure of 0.5 MPa for 20 min. After cooling to 30°C, melt them with an electric heating wire fuser. The heating wire temperature is 320°C, the fusing interval is 1 cm, and the fusing method is orthogonal fusing. Rinse with a 5°C sodium bicarbonate solution of 8% by mass for 3 min, wash with pure water 5 times, and dry at 70°C for 6 h to obtain an antibacterial agent.

[0046] (4) Packaging: The antimicrobial agent is put into packaging paper and packaged into bags using a packaging machine. The packaging weight of each bag is 4 g, thereby obtaining a high temperature resistant and long-lasting antimicrobial agent.

[0047] Comparative Example 1

[0048] A high temperature resistant and durable antibacterial agent mainly comprises, by weight, 5 parts of polymer film, 150 parts of organosilicon deposition liquid and 1 part of silver nitrate solution.

[0049] A method for preparing a high temperature resistant and long-lasting antibacterial agent, the method for preparing the high temperature resistant and long-lasting antibacterial agent mainly comprises the following preparation steps:

[0050] (1) Primary deposition: 8-amino-1-octene, iodomethane and 10% sodium hydroxide solution were mixed in a mass ratio of 1:5:3, and then 0.01 times the mass of 8-amino-1-octene sodium iodide was added, and the mixture was stirred at 30°C and 500 r / min for 6 hours, and then heated to 50°C and maintained for 30 minutes, cooled to 1°C and filtered, and rinsed with 1°C 8% sodium bicarbonate solution for 5 minutes, and then washed with 1°C pure water for 5 times, and dried at 1Pa, -10°C for 8 hours to obtain octenyl quaternary ammonium salt, and octenyl quaternary ammonium salt and anhydrous ethanol were mixed in a mass ratio of 3:10, and then 0.01 times the mass of octenyl quaternary ammonium salt was added. The catalyst prepared by mixing titanium tetrachloride and triethylaluminum in a mass ratio of 5:3 was deposited at 50°C to obtain a straight deposition film with a thickness of 0.5 mm, and then washed with anhydrous ethanol for 3 times, and dried at 60°C for 6 hours to obtain a polymer film;

[0051] (2) Secondary deposition: The polymer film was fixed on a glass plate and treated with an organic silicon deposition liquid. Ethyl orthosilicate, 10% ammonia water and anhydrous ethanol were mixed in a mass ratio of 1:10:10 to prepare an organic silicon deposition liquid. The surface was soaked with an organic silicon deposition liquid 0.8 times the mass of the polymer film. The surface was irradiated with an ultraviolet lamp with a power of 60 W and a wavelength of 300 nm at 20°C for 10 min. The surface was immersed in an organic silicon deposition liquid 20 times the mass of the polymer film. The surface was allowed to stand at 20°C for 2 h. The polymer film was turned over so that the surface not treated with the organic silicon deposition liquid was facing up and fixed on a glass plate. The organic silicon deposition liquid treatment steps were repeated. The polymer film was then rinsed with 10% sodium hydroxide for 20 min. The surface was washed with pure water and anhydrous ethanol three times in sequence. The surface was dried at -10°C and a pressure of 5 Pa for 8 h to obtain a composite film.

[0052] (3) Hot-pressing fusing: soak one side of the composite membrane with a 10% silver nitrate solution of 0.3 times the mass of the composite membrane, place the wetted surfaces of the two composite membranes together, press at 100°C and a pressure of 0.3 MPa for 30 min, cool to 10°C and then fuse with an electric heating wire fuser, the heating wire temperature is 300°C, the fuse spacing is 1 cm, and the fuse mode is orthogonal fusing. Rinse with 1°C sodium bicarbonate solution of 8% by mass for 5 min, wash with pure water 3 times, and dry at 60°C for 8 h to obtain an antibacterial agent.

[0053] (4) Packaging: The antimicrobial agent is put into packaging paper and packaged into bags using a packaging machine. The packaging weight of each bag is 3 g, thereby obtaining a high temperature resistant and long-lasting antimicrobial agent.

[0054] Comparative Example 2

[0055] A high temperature resistant and durable antibacterial agent mainly comprises, by weight, 5 parts of modified polymer film and 1 part of silver nitrate solution.

[0056] A method for preparing a high temperature resistant and long-lasting antibacterial agent, the method for preparing the high temperature resistant and long-lasting antibacterial agent mainly comprises the following preparation steps:

[0057] (1) Deposition: 8-amino-1-octene, iodomethane and 10% sodium hydroxide solution were mixed in a mass ratio of 1:5:3, and then 0.01 times the mass of 8-amino-1-octene sodium iodide was added, and the mixture was stirred at 30°C and 500 r / min for 6 hours, and then heated to 50°C and maintained for 30 minutes, cooled to 1°C and filtered, rinsed with 1°C 8% sodium bicarbonate solution for 5 minutes, and then washed with 1°C pure water for 5 times, and dried at 1Pa, -10°C for 8 hours to obtain octenyl quaternary ammonium salt. Octenyl quaternary ammonium salt, acrylic acid and anhydrous ethanol were mixed in a mass ratio of 3:1:10, and then 0.01 times the mass of octenyl quaternary ammonium salt was added. The catalyst prepared by mixing titanium tetrachloride and triethylaluminum in a mass ratio of 5:3 was deposited at 50°C to obtain a straight deposition film with a thickness of 0.5 mm, and then washed with anhydrous ethanol for 3 times, and dried at 60°C for 6 hours to obtain a modified polymer film;

[0058] (2) Hot-pressing fusing: soak one side of the modified polymer film with a 10% silver nitrate solution of 0.3 times the mass of the modified polymer film, and place the wetted surfaces of two modified polymer films together. Press them at 100°C and a pressure of 0.3 MPa for 30 min. After cooling to 10°C, melt them with a heating wire fusing machine. The heating wire temperature is 300°C, the fusing interval is 1 cm, and the fusing method is orthogonal fusing. Rinse with a 1°C sodium bicarbonate solution of 8% by mass for 5 min, wash with pure water 3 times, and dry at 60°C for 8 h to obtain the antibacterial agent.

[0059] (3) Packaging: The antimicrobial agent is put into packaging paper and packaged into bags using a packaging machine. The packaging weight of each bag is 3 g, thereby obtaining a high temperature resistant and long-lasting antimicrobial agent.

[0060] Comparative Example 3

[0061] A high temperature resistant and durable antibacterial agent mainly comprises, by weight, 5 parts of polymer film and 1 part of silver nitrate solution.

[0062] A method for preparing a high temperature resistant and long-lasting antibacterial agent, the method for preparing the high temperature resistant and long-lasting antibacterial agent mainly comprises the following preparation steps:

[0063] (1) Deposition: 8-amino-1-octene, iodomethane and 10% sodium hydroxide solution were mixed in a mass ratio of 1:5:3, and then 0.01 times the mass of 8-amino-1-octene sodium iodide was added, and the mixture was stirred at 30°C and 500 r / min for 6 hours, and then heated to 50°C and maintained for 30 minutes, cooled to 1°C and filtered, rinsed with 1°C 8% sodium bicarbonate solution for 5 minutes, and then washed with 1°C pure water for 5 times, and dried at 1Pa, -10°C for 8 hours to obtain octenyl quaternary ammonium salt, and octenyl quaternary ammonium salt and anhydrous ethanol were mixed in a mass ratio of 3:10, and then 0.01 times the mass of octenyl quaternary ammonium salt was added. The catalyst prepared by mixing titanium tetrachloride and triethylaluminum in a mass ratio of 5:3 was deposited at 50°C to obtain a straight deposition film with a thickness of 0.5 mm, and then washed with anhydrous ethanol for 3 times, and dried at 60°C for 6 hours to obtain a polymer film;

[0064] (2) Hot-pressing fusing: soak one side of the polymer film with a 10% silver nitrate solution of 0.3 times the mass of the polymer film, and place the wetted surfaces of the two polymer films together. Press them at 100°C and a pressure of 0.3 MPa for 30 min. After cooling to 10°C, melt them with a heating wire fusing machine. The heating wire temperature is 300°C, the fusing interval is 1 cm, and the fusing method is orthogonal fusing. Rinse with a 1°C sodium bicarbonate solution of 8% by mass for 5 min, wash with pure water 3 times, and dry at 60°C for 8 h to obtain the antibacterial agent.

[0065] (3) Packaging: The antimicrobial agent is put into packaging paper and packaged into bags using a packaging machine. The packaging weight of each bag is 3 g, thereby obtaining a high temperature resistant and long-lasting antimicrobial agent.

[0066] Effect example

[0067] Table 1 below shows the analysis results of the antibacterial properties and high temperature resistance durability of the high temperature resistant and durable antibacterial agents of Examples 1 to 3 of the present invention and Comparative Examples 1 to 3.

[0068] Table 1

[0069] Antibacterial rate Performance retention rate Antibacterial rate Performance retention rate Example 1 99.8% 99.2% Comparative Example 1 99.9% 88.5% Example 2 99.9% 99.3% Comparative Example 2 92.7% 95.2% Example 3 99.8% 99.3% Comparative Example 3 90% 83.5%

[0070] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 1 in Table 1, it can be found that the performance retention rate of Examples 1, 2, 3 compared with Comparative Example 1 is increased, which shows that in the process of preparing the polymer film with octenyl quaternary ammonium salt, acrylic acid is added to modify the polymer film to obtain a modified polymer film, and the quaternary ammonium cations on the modified polymer film can be combined with the carboxyl anions through electrostatic force, which prevents the quaternary ammonium cations from swinging randomly under high temperature environment and the long carbon chain connected to the main chain from being easily broken, thereby making the material have high temperature resistance; From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 2, it can be found that the performance retention rate of Examples 1, 2, 3 compared with Comparative Example 1 is increased. The antibacterial rate and performance retention rate of Example 2 increased, indicating that the porous silica gel surface formed after the secondary deposition has good water absorption, which makes the surrounding environment dry to achieve the antibacterial effect, and at the same time has a good adhesion effect to stabilize the antibacterial agent structure, and has a good binding ability to silver nitrate, which prevents the rapid loss of silver nitrate, thereby improving the high temperature resistance and durability of the material; the antibacterial rate and performance retention rate of Examples 1, 2, and 3 compared with Comparative Example 3 increased, indicating that the addition of acrylic acid modification and secondary deposition in the process of preparing the polymer film with octenyl quaternary ammonium salt can significantly improve the antibacterial property and high temperature resistance and durability of the material.

[0071] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A high temperature resistant and durable antibacterial agent, characterized in that: In terms of weight, it mainly includes: 4 parts of modified polymer film, 200 parts of organic silicon deposition liquid and 1 part of silver nitrate solution; The preparation method of the high temperature resistant and durable antibacterial agent mainly comprises the following preparation steps: (1) Primary deposition: 8-amino-1-octene, iodomethane and 10% sodium hydroxide solution were mixed in a mass ratio of 1:5:3, and then 0.02 times the mass of 8-amino-1-octene sodium iodide was added. The mixture was stirred at 35°C and 600 r / min for 5 h, then heated to 55°C and maintained for 25 min, cooled to 3°C and filtered, rinsed with 3°C 8% sodium bicarbonate solution for 4 min, and then washed with 3°C pure water for 4 times. Drying for 7 hours at 5Pa and -5°C to obtain octenyl ammonium salt, mixing octenyl ammonium salt, acrylic acid and anhydrous ethanol in a mass ratio of 3:1:10, adding 0.01-0.03 times the mass of octenyl ammonium salt and a catalyst prepared by mixing titanium tetrachloride and triethylaluminum in a mass ratio of 5:3, depositing at 55°C to obtain a straight deposition film with a thickness of 0.6 mm, washing with anhydrous ethanol for 4 times, and drying at 65°C for 5 hours to obtain a modified polymer film; (2) Secondary deposition: The modified polymer film was fixed on a glass plate and treated with an organic silicon deposition liquid. Ethyl orthosilicate, 10% ammonia water and anhydrous ethanol were mixed in a mass ratio of 1:10:10 to prepare an organic silicon deposition liquid. The surface was soaked with an organic silicon deposition liquid of 0.1 times the mass of the modified polymer film. The surface was irradiated with an ultraviolet lamp with a power of 65 W and a wavelength of 340 nm at 25°C for 9 minutes. The surface was immersed in an organic silicon deposition liquid of 23 times the mass of the modified polymer film. The surface was allowed to stand at 25°C for 1 hour. The modified polymer film was turned over so that the surface not treated with the organic silicon deposition liquid faced upward and was fixed on a glass plate. The organic silicon deposition liquid treatment steps were repeated. The surface was then rinsed with 10% sodium hydroxide for 25 minutes. The surface was washed with pure water and anhydrous ethanol four times in sequence. The surface was dried at -5°C and a pressure of 8 Pa for 7 hours to obtain a composite film. (3) Hot-pressing fusing: soak one side of the composite membrane with a 10% silver nitrate solution of 0.4 times the mass of the composite membrane, and place the wetted surfaces of the two composite membranes together. Press them at 110°C and 0.4 MPa for 25 min. After cooling to 20°C, melt them with a heating wire fusing machine. The heating wire temperature is 310°C, the fusing interval is 1 cm, and the fusing method is orthogonal fusing. Rinse with a 3°C sodium bicarbonate solution of 8% by mass for 4 min, wash with pure water 4 times, and dry at 65°C for 7 h to obtain the antibacterial agent. (4) Packaging: The antimicrobial agent is put into packaging paper and packaged into bags using a packaging machine. The packaging weight of each bag is 3 g, thereby obtaining a high temperature resistant and long-lasting antimicrobial agent.

Citation Information

Patent Citations

  • Method for preparing cotton fabric loaded with organosilicon quaternary ammonium and nano titanium dioxide composite antibacterial agent

    CN102677453A

  • Preparation method of nano-silver antibacterial agent

    CN107232229A